The Transformation of Critical Land Governance Based on the Islamic Spirituality Values - Muslih, Moh.; Aenurofik (JURNAL PENELITIAN, 2022)
The study aims to transform the critical land governance based on the Islamic spirituality values which contained in the societies economic and environmental conservation values. This study used the Participatory Action Research (PAR) method, it was taken by two stages, in each stage there were four procedures. The study involved the society at Dawuhan village, on Sirampong district, in Brebes regency, as teamwork to solve the critical land problem. The result of this study showed that coffee planting as transformation of critical land governance. It transformations based on the environmental conservation and the society’s economic values. After the transformation of critical land governance, the environmental conservation values showed that the critical land in Dawuhan village decreased, meanwhile the society’s economic values in Dawuhan village greatly increased. The critical land reduced, it shown by hard crops (pine, coffee, and etc.) planted in great numbers from 20% to 30%. The progress in economic values also shown by coffee yields, it increased from 1 ton to 5 tons. Alongs woith PAR method implemented in this study, the hard crops and the economy growth.